Geoelectrical mapping of contamination in the cemeteries: the case study in Piracicaba, São Paulo/Brazil - da Costa Silva, Robson Willians; Malagutti Filho, Walter [UNESP] (Springer, 2012)
This paper presents the results of electrical resistivity methods in the area delineation that was potentially contaminated by liquefaction products, which are also called putrefactive liquids in Vila Rezende municipal cemetery, Piracicaba, So Paulo, Brazil. The results indicate a depth of water table between 3.1 and 5.1 m, with two groundwater direction flows, one to the SW and another to the SE. Due to the contamination plumes, which have the same groundwater direction flow, as well the conductive anomalies observed in the geoelectric sections, the contamination suspicions in the area were confirmed. The probable plume to the SE extends beyond the limits of the cemetery. The location of the conductive anomalies and the probable contamination plumes showed that the contamination is linked with the depth of the water table and the burial time. Mapping using the geostatistical method of ordinary kriging applied to the work drew structural characteristics of the regional phenomenon and spatial behavior of the electrical resistivity data, resulting in continued surfaces. Thus, this method has proved to be an important tool for mapping contamination plumes in cemeteries.
Keywords: Cemeteries; Electrical resistivity; Contamination plume; Geostatistics; Ordinary kriging